Reinvenções do nordeste no cinema brasileiro contemporâneo: masculinidades desviadas, estéticas subversivas e encruzilhadas do tempo - Nascimento, Samuel Macêdo do (2024)
This thesis investigates the historical and cultural tensions in contemporary cinema of the Brazilian Northeast, highlighting how 21st-century films present a Northeast with distinct imaginaries, landscapes, bodies, and discourses. Analyzing works such as Tatuagem (2013), Praia do Futuro (2014), Boi Neon (2015), and Bacurau (2019), the research categorizes these films as “counter-cinema.” This category questions the reinventions of the Northeast in contemporary Brazilian cinema, emphasizing deviant masculinities and aesthetics that subvert the traditional model of the northeastern man. The myths and ghosts of the “cabra-macho” continue to haunt northeastern culture, but contemporary cinema brings new layers that update these norms and materialize deviations from the normative figure of the “man.” The editing in the films creates a phantasmagoric clash, opening multiple fronts of interpretation simultaneously. Film analysis brings us closer to multiple references and a rhizomatic archive, in addition to stressing the limits of each work (BRENEZ, 2014). From the temporal crossroads (Didi-Huberman, 2015), we connect the ancestral influences and technologies that have always been present with those brought by the phenomenon of the diaspora, within the territorial limit known as the Northeast.